SUATU TELAAH MENGENAI SISTEM PEMASYARAKATAN DI LAPAS DILIHAT DARI ASPEK SISTEM PERADILAN PIDANA - Iman Hidayat (Universitas Batanghari Jambi, 2014)
The total criminality in the society is getting more (and more. There is indicatoion that the criminality incresing in the society is coused by failure of criminal justice system the one of it is society institution. The primer data indicates that the failure happens to be coused by regulation, officer, fasilities and society factor.Research indicates that the erection execution of prisoner done in the society institution grade needs to be equiped by profesional officer and special erection programme prisoner likes: Religious erection activity, the erection of low consciousness for there are in the society.Keyword : system has begun, justice, criminal